THE ANALYSIS OF INTERNAL FACTORS AFFECTING THE LIQUIDITY OF SOVEREIGN SUKUK IN INDONESIA - Arien Rosetika; Salahuddin El Ayyubi; Widyastutik Widyastutik (Universitas Airlangga, 2020)
Indonesian sovereign Sukuk has lower liquidity than the foreign bond. Sukuk liquidity is measured by total return and trade volume in the secondary market from June 2015 until May 2017. This study aims to analyze the internal determinant factors of sovereign Sukuk liquidity in Indonesia. The method used in this study is Panel Data analysis. The variables used in this study are liquidity, outstanding, coupon rate, time to maturity and age. The study results show that outstanding is significantly positive as the determinant of liquidity of sovereign Sukuk in Indonesia. Variables of time to maturity and age are significantly negative as the determinant of liquidity of sovereign Sukuk in Indonesia. Meanwhile, the coupon rate variable is not significant as the determinant of liquidity of sovereign Sukuk in Indonesia. Keywords: Liquidity, Outstanding, Coupon Rate, Time to Maturity, Age, Sovereign Sukuk, Panel Data AnalysisREFFERENCE Accounting and Auditing Organization for Islamic Financial Institutions. (2003). Sukuk [Internet]. [diunduh 2016 Nov 22]. Tersedia pada: http://www.aaoifi.com.Alexander GJ, Edwards AK, Ferri MG. (2000). The determinants of trading volume of high yield corporate bonds. Journal of Financial markets, 3(1), 177-204.Bao J, Pan J, Wang J. (2008). Liquidity of corporate bonds. Journal of Financial Economics 44(1): 628-650.Badan Pengawas Pasar Modal dan Lembaga Keuangan. (2009). Keputusan BAPEPAM No.123/BAPEPAM/LK/IX/2009 tentang Efek Syariah. Jakarta (ID): Badan Pengawas Pasar Modal dan Lembaga Keuangan.Bursa Efek Indonesia. (2015). IDX monthly statistics Juni – Desember 2015 [Internet]. [diunduh 2017 Sep 22]. Tersedia pada: http://www.bei.go.id.Bursa Efek Indonesia. (2016). IDX monthly statistics Januari – Desember 2016 [Internet]. [diunduh 2017 Sep 22]. Tersedia pada: http://www.bei.go.id.Bursa Efek Indonesia. (2017). IDX monthly statistics Januari – Mei 2017 [Internet]. [diunduh 2017 Sep 22]. Tersedia pada: http://www.bei.go.id.Bursa Efek Indonesia. (2017). IDX statistics 1st quarter 2017 [Internet]. [diunduh 2017 Sep 22]. Tersedia pada: http://www.bei.go.id.Bursa Efek Indonesia. (2017). Indonesia bond indexes fact sheet Juli 2017 [Internet]. [diunduh 2017 Sep 22]. Tersedia pada: http://www.bei.go.id.Bank Indonesia. (2017). Data outstanding sukuk negara 2006-2017 [internet]. [diunduh 2017 Juli 28]. Tersedia pada: http://www.bi.go.idBunaidy MR. (2012). Analisis Deskriptif Likuiditas Obligasi Pemerintah Republik Indonesia. Tesis tidak diterbitkan. Depok: Universitas Indonesia.Direktorat Jenderal Pengelolaan Pembiayaan dan Resiko. (2015). Outstanding Surat Berharga Negara 2015 [Internet]. [diunduh 2017 Sep 22]. Tersedia pada: http://www.djppr.go.id Direktorat Jenderal Pengelolaan Pembiayaan dan Resiko. (2015). Sukuk Negara: Instrumen Keuangan Berbasis Syariah. Jakarta: Kementrian Keuangan.Direktorat Jenderal Pengelolaan Pembiayaan dan Resiko. (2016). Course on sukuk: sharia and operational aspects. Jakarta: Kementrian Keuangan.Direktorat Jenderal Pengelolaan Pembiayaan dan Resiko. (2016). Outstanding Surat Berharga Negara 2016 [Internet]. [diunduh 2017 Sep 22]. Tersedia pada: http://www.djppr.go.idDirektorat Jenderal Pengelolaan Pembiayaan dan Resiko. (2017). Istilah umum terkait dengan investasi pada Surat Utang Negara. Jakarta: Kementrian keuanganDirektorat Jendral Pengelolaan Pembiayaan dan Resiko. (2017). Outstanding Surat Berharga Negara 2017 [Internet]. [diunduh 2017 Sep 22]. Tersedia pada: http://www.djppr.go.idDewan Syariah Nasional Majelis Ulama Indonesia. (2002). Fatwa DSN No.32/DSN-MUI/MUI/IX/2002 tentang Obligasi Syariah. Jakarta: Dewan Syariah Nasional MUI.Elton EJ, Gruber MJ, Agrawal D. (2002). Factors Affecting the Valuation of Corporate Bonds [Working Paper]. New York, USA: New York University.Ericsson J, Renault O. (2001). Liquidity and Credit Risk. Journal ofFinance, 6(1), 2219-2250.Fabozzi, FJ. 2000. Manajemen investasi. Jakarta: Salemba 4.Fatah DA. (2011). Perkembangan obligasi syariah (sukuk) di Indonesia: Analisis peluang dan tantangan. Jurnal Al-‘Adalah, 10(1), 35-45. Firdaus M. (2011). Aplikasi ekonometrika untuk data panel dan time series. Bogor: IPB Pr.Friewald N, Jankowitsch R, Subrahmanyam MG. (2010). Illiquidity or credit deterioration: A study of liquidity in the US corporate bond market during financial crises. Journal of Financial Economics, 105(2), 18-36.Gujarati D. (2003). Ekonometrika dasar. Jakarta: Erlangga.Hariyanto. (2010). Sukuk Negara Ritel [Internet]. [diunduh 2017 Nov 3]. Tersedia pada: http://www.ojk.go.id.Harris, Said R, Suhaimi WN. (2012). Determinants of Islamic Bonds (Sukuk): Evidence in Malaysia. Malaysian Journal of Accounting Research, 3(1), 123-133.Hastin M, Idris, Aimon H. (2013). Analisis pasar obligasi pemerintah di Indonesia. Jurnal Kajian Ekonomi, 1(1), 12-22.Houweling P, Mentink A, Vorst T. (2004). Comparing possible proxies of corporate bond liquidity. Journalof Banking & Finance, 29(1), 1331-1358.Huang GC, Liano K, Pan MS. (2013). The Information Content of Stock Splits. Journal of Empirical Finance, 16(4), 557-567.Huang JY, Wang SS, Huang JM. (2013). Empirical Analysis of Liquidity Risk Premium Based on Bond Age. WSEAS Transaction on Business and Economics, 10(4), 316-325.Huda, Nasution ME. (2007). Investasi pada pasar modal syariah. Jakarta: Prenada Media Grop.Juanda B, Junaidi. (2012). Ekonometrika deret waktu teori dan aplikasi. Bogor: IPB Press.Mahanti S, Chacko G, Malik G. (2005). The determinants of liquidity in the corporate bond markets: an application of latent liquidity. Journal of Financial Economics, 88(1), 272-298.Mahanti S, Nashikkar A, Subrahmanyam M. (2008). Latent liquidity: a new measure of liquidity, with an application to corporate bonds. Journal of Financial Economics, 7(1), 211-233.Manurung AH, Adianto D. (2011). Analisis faktor-faktor yang memengaruhi likuiditas obligasi. Journal of Accounting Research, 6(1), 123-133.McGinty L. (2001). Issue size versus liquidity in credit. J.P. Morgan Fixed Income Research, 19(2), 61-77.Nafik, M. (2008). Bursa efek dan investasi syariah. Jakarta: Sinar Grafika.